Challenges in Against DHF in the Tropical Area - Budi Joko Santosa (Health Notions, 2020)
Morbidity of Dengue Hemorrhagic Fever is the interaction between viruses, vulnerable hosts and mosquitoes in risky environments, what about rational management in the tropics? DHF agents are dengue virus, family Flaviridae, genus Flavivirus, serotypes Den-1, Den-2, Den3 and Den-4. Virulence of four virus serotypes has been found in fatal cases. The extrinsic incubation period of 8-10 days, intrinsic in humans 4-6 days, is transmitted from male mosquitoes to female mosquitoes through marriage, transovarial transmission from parent mosquitoes to their offspring. Highest transmission through mosquito bites Ae. Aegypti. Hosts 95% aged 15-44 years. Host immunity is influenced by age, nutritional status, density, population mobility, housing quality, distance between houses, education, work, life attitudes, age group, ethnicity, and vulnerability. Aedes mosquitoes originating from Brazil and Ethiopia, have two subspecies; Ae aegypti queenslandensis and Ae. aegypti formosus, including Stegomya subgenus, Aedes aegypti and Ae mosquitoes. albopictus as the main vector and Ae. polynesiensis, Ae.scutellaris and Ae (Finlaya) niveus as secondary vectors. Transmission factors are rapid urban population growth, population mobilization, poverty, garbage disposal, drying and closing, and recycling, the habit of hanging clothes. In the tropics, incidence is correlated with rainfall and humidity. Tropical and subtropical characteristics allow DHF to be endemic.Keywords: management; dengue hemorrhagic fever; tropical